Preparation of Activated Carbon Derived from Jordanian Olive Cake and Functionalized with Cu/Cu2O/CuO for Adsorption of Phenolic Compounds from Olive Mill Wastewater - Muna Abu-Dalo (MDPI AG, 2021)
Olive oil production generates solid and liquid wastes that cause various environmental problems due to their high phenols and polyphenols load. Although many treatment methods were investigated to manage these wastes, more research is still needed to identify simple and cost-effective approaches. In this study, activated carbon (AC) was prepared from olive cake waste and functionalized with Cu/Cu2O/CuO for efficient and selective removal of phenolic content from olive mill wastewater (OMW). AC media were characterized by scanning electron/dispersive X-ray spectroscopy (SEM-EDS), X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectrometry, and Brunauer–Emmett–Teller (BET) surface area analysis. The optimum adsorption parameters were investigated, and the adsorption isotherms, thermodynamics, and kinetics were determined. The adsorption of phenols onto copper oxide AC was best described by the Langmuir adsorption with maximum adsorption capacity of 13.9, 12.7, and 9.9 mg/g at 311, 302, and 293 K, respectively. The adsorption reaction was found to be spontaneous and endothermic where ∆H° and ∆G° were found to be 30.104 kJ/mol and −1.765, −2.839, and −3.723 (kJ/mol) at 311, 302, and 293 K, respectively. In addition, the kinetics data were perfectly fit by the pseudo-second-order model. The activated product derived from recyclable olive cake and enriched with inorganic functionality can offer a cost-effective treatment solution for OMW; thus, reducing both the liquid and solid waste generated from the olive mill industry.